2014
DOI: 10.1155/2014/502370
|View full text |Cite
|
Sign up to set email alerts
|

Culture versus PCR forSalmonellaSpecies Identification in Some Dairy Products and Dairy Handlers with Special Concern to Its Zoonotic Importance

Abstract: A total of 200 samples of milk and dairy products as well as 120 samples of dairy handlers were randomly collected from different dairy farms and supermarkets in Dakahlia Governorate, Egypt. The conventional cultural and serotyping methods for detection of Salmonella in dairy products were applied and the results were compared with those obtained by molecular screening assay using (ttr sequence). The obtained results revealed that 21% of milk and dairy products (42/200) were positive for Salmonella species usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
5
17
0
Order By: Relevance
“…Different studies have shown very high prevalence rate of Salmonella contamination of vegetables [8,14] and different animal products [6,21,22]. The prevalence rates from these studies compares favorably with the 20% of the 120 study samples and the 96% of the 25 pure Salmonella isolates of DNA-PCR Salmonella invA gene detectable results obtained in this current study.…”
Section: Discussionsupporting
confidence: 76%
“…Different studies have shown very high prevalence rate of Salmonella contamination of vegetables [8,14] and different animal products [6,21,22]. The prevalence rates from these studies compares favorably with the 20% of the 120 study samples and the 96% of the 25 pure Salmonella isolates of DNA-PCR Salmonella invA gene detectable results obtained in this current study.…”
Section: Discussionsupporting
confidence: 76%
“…Apparently, the methods were not fast enough to keep up with the pace of animal food production. In the last decades, several PCR-based methods that include PCR [9], PCR in combination with hybridization [10], immuno-PCR by combining monoclonal antibody coated magnetic bead with PCR [11], PCR in combination with conventional culture and serotyping [12] and real-time PCR [13][14][15][16][17][18] for rapid detection of Salmonella have been reported. However, all of these methods require a pre-enrichment step of 6-28h followed by tedious DNA isolation and purification procedures to overcome PCR inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…At Bahir Dar University, 2.7% of the food handlers tested positive for S. Typhi [7]. Additionally, studies performed amongst food handlers in Ethiopia in the southern region, University of Gondar, dairy workers, and Addis Abbaba University showed prevalence of 3.1%, 0.93%, 5.0%, 4.8% respectively [2] [6] [10] [11]. A 2015 study by David et al at a Nigerian university showed a prevalence of 35% amongst food handlers following a recent outbreak of typhoid fever [12].…”
Section: Introductionmentioning
confidence: 97%
“…Several thousand non-typhoidal serovars exist with the predominant strains varying from region to region but the most common serovars being Salmonella enteritidis (S. enteritidis) and Salmonella typhimurium (S. Typhimurium) which comprise approximately three-quarters of the global yearly cases of salmonellosis [2] [3]. Typhoidal Salmonella, divided into serovars Salmonella typhi (S. typhi) and Salmonella paratyphi (S. paratyphi), as the names suggest, are the cause of typhoid fever [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation